Advances in Imaging for Atrial Fibrillation Ablation. (4th January 2011) - D'Silva, Andrew; Wright, Matthew
Abstract : Over the last fifteen years, our understanding of the pathophysiology of atrial fibrillation (AF) has paved the way for ablation to be utilized as an effective treatment option. With the aim of gaining more detailed anatomical representation, advances have been made using various imaging modalities, both before and during the ablation procedure, in planning and execution. Options have flourished from procedural fluoroscopy, electroanatomic mapping systems, preprocedural computed tomography (CT), magnetic resonance imaging (MRI), ultrasound, and combinations of these technologies. Exciting work is underway in an effort to allow the electrophysiologist to assess scar formation in real time. One advantage would be to lessen the learning curve for what are very complex procedures. The hope of these developments is to improve the likelihood of a successful ablation procedure and to allow more patients access to this treatment.